Analisis Dampak Positif terhadap Kesejahteraan dan Pertumbuhan Ekonomi dalam Penerapan Konsep Desa Wisata di Desa Batulayang, Kabupaten Bogor - Yudhiet Fajar Dewantara; Prayogo Susanto (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
In 2013 village Batulayang subdistrick Cisarua, distric Bogor West Java into tourist village because dates from outbound managed by the local people. The purpose of this research objectives is to determine the positive impact on welfare and economic growth with the application of the concept of tourist village in the village Batulayang, Bogor Districts, West Java. Research methods that were used to the research is the quantitative methods with Cartesian used diagrams of evidence. In this research researchers uses a questionnaire that will be distributed to resident of the village of Batulayang. The result and the discussion in a quadrant I namely foreign exchange earnings having a high priority because if there are guests foreign tourists and experienced a lack of financial in rupiah, so foreign tourists can use the currencies of his country in cash and bank which is to use. In a quadrat II to, government revenues employment generation, and development of local economies in dimension which means the means the means to uphold are very important. In a quadrant III, no in other words no effect on economic growth. On quadrant IV infrastructure development in a quadrant is considered less important because tourists be preoccupied with activities in the village and the tourist will use smartphone, before going to sleep but to signal and electricity are adequate. The conclusions researchers is tourist village very helpful for the economy residents and can grow economy. As a suggestion the government can cooperate with Batulayang village and private sector to create artificial attraction in Batulayang village to build marketing in the village and increase a vacancy for local residents.